Effect of Inhaled Prostaglandin E2 on Methacholine and Leukotriene D4 Airway Responsiveness in Asthmatic Subjects - Wil Hm Stevens; Cheryl P VanderHeyden; Paul M O'Byrne (Canadian Respiratory Journal)
Previous studies in asthmatics have demonstrated that the endogenous release of inhibitory prostaglandins limits the bronchoconstrictor response to repeated challenges with exercise and histamine, and that inhaled prostaglandin (PG) E2 attenuates allergen-induced asthmatic responses and exercise bronchoconstriction in asthmatics. Inhaled PGE2 does not significantly attenuate methacholine airway responsiveness. These results, taken together, indicate that inhaled PGE2 attenuates the bronchoconstriction caused by stimuli, such as allergen and exercise, that result in bronchoconstriction through cysteinyl leukotriene (LT) release. The purpose of this study was to determine whether inhaled PGE2 could selectively attenuate LTD4-induced bronchoconstriction in seven stable asthmatic subjects. Each subject was studied on four different study days. On two occasions the subjects inhaled 100 mg PGE2, 30 mins before a methacholine, or LTD4 challenge test. On the other two study days, the subjects were pretreated with its diluent. Results were expressed as the provocation concentration causing a 20% fall in forced expiratory volume in 1 s (FEV1) (PC20). PGE2 pretreatment significantly increased the LTD4 PC20, but not the methacholine PC20. The mean LTD4 PC20 increased from 2.00 mg/mL (%SEM 1.65) after diluent pretreatment to 3.01 mg/mL (%SEM 1.64) after PGE2 pretreatment (P=0.008). The mean methacholine PC20 was 1.28 mg/mL (%SEM 1.68) after diluent pretreatment and 1.62 mg/mL (%SEM 1.46) after PGE2 pretreatment (P=0.28). These results suggest that PGE2 partially attenuates LTD4-induced bronchoconstriction; however, the magnitude of the effect is unlikely to account for its attenuation of exercise and allergen-induced bronchoconstriction.